Exploration of Characteristics Governing Dynamics of Whirlwinds: Application to Dust Devils - Pandey S.K.; Maurya J.P. (My University, 2025)
It is intended to model mathematically an ideal whirlwind which characterises this geo-physical phenomenon and eventually helps us decode the inherent dynamics. A dense cylindrical aerial mass is taken into consideration surrounding a rarer aerial region in order to keep a radial favourable gradient of pressure to sustain a rotational motion. It has been concluded that the whirlwind will survive as long as the low pressure region exists. The vertical pressure gradient also plays an equally important role. Since it is not connected to any cloud and the axial velocity is in the vertically upward direction, the momentary vertical gradient of pressure is required for its growth and survival. Horizontal ambient winds that rush towards low pressure zone, crush the air in the buffer zone, and turn vertically upward may also take the dust carried with them visibly to some height. It is considered that the angular azimuthal velocity varies within the annulus. An inference is that no whirlwind without a low pressure region within it can survive. This may be termed as the fundamental characteristic of whirlwind. It is further concluded that if the radial pressure difference between the outermost and innermost layers is larger, the whirlwind is thicker and consequently, it will last longer. Moreover, another conclusion arrived at is that the angular velocity will vanish if the inner radius is zero. © 2017 Walter de Gruyter GmbH, Berlin/Boston.